Royal Jelly Components Encapsulation in a Controlled Release System-Skin Functionality, and Biochemical Activity for Skin Applications - Eleni Spanidi; Sophia Athanasopoulou; Angeliki Liakopoulou; Angeliki Chaidou; Sophia Hatziantoniou; Konstantinos Gardikis (MDPI AG, 2022)
Royal jelly is a yellowish-white substance with a gel texture that is secreted from the hypopharyngeal and mandibular glands of young worker bees. It consists mainly of water (50-56%), proteins (18%), carbohydrates (15%), lipids (3-6%), minerals (1.5%), and vitamins, and has many beneficial properties such as antimicrobial, anti-inflammatory, anticancer, antioxidant, antidiabetic, immunomodulatory, and anti-aging. Royal jelly has been used since ancient times in traditional medicine, cosmetics and as a functional food due to its high nutritional value. The main bioactive substances are royalactin, and 10-hydroxy-2-decenoic acid (10-HDA). Other important bioactive molecules with antioxidant and photoprotective skin activity are polyphenols. However, they present difficulties in extraction and in use as they are unstable physicochemically, and a higher temperature causes color change and component degradation. In the present study, a new encapsulation and delivery system consisting of liposomes and cyclodextrins incorporating royal jelly has been developed. The new delivery system aims to the elimination of the stability disadvantages of royal jelly's sensitive component 10-HDA, but also to the controlled release of its ingredients and, more particularly, 10-HDA, for an enhanced bioactivity in cosmeceutical applications.